Financial control at the stage of sanctioning in the process of financing to national target programs: the content and characteristic of the main elements - Пивовар, Юрій Ігорович; Пашинська, Вікторія Вікторівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The main idea of this article is to identify the characteristics of display elements of the semantic concept of financial control at the stage of sanctioning in the funding of national target programs. At baseline author identified seven main elements, by which was carried further analysis of the content of specific financial control in specified stages. First, the tasks of financial control. Formulated three general groups: a) strategic objectives; b) tactical tasks; c) operational tasks. Second, financial control functionsdefined as follows: a) information; b) analytical; c) Stability; d) law enforcement; d) preventive (warning); e) educational function. Thirdly, object of financial control in the sphere of financing of national target programs is defined by the distribution of all the financial activities of authorized subjects over the distribution of expenditure on measures and objectives of national target programs. Fourth, from subject matter to financial control include documentation that the subjects used in the process of distribution of public (government) funds to cover government expenditures on targeted measures. Fifthly, the main methods of investigational Control is named: a) expertise; b) examination (examinations); c) analysis method;. d) monitoring (monitoring); e) registration and accounting; f) inspection; g) revision. Sixth, the system controlled of subjects are presented in groups, are: 1) the initiators of national target programs; 2) the contracting authorities; 3) the public authorities in the status of budget funds and / or of responsible budget programs; 4) competitive performers program activities and objectives; 5) other state authorities within the powers that organize and manage the process of budget allocation to cover spending needs to implement national target programs financing activities. Seventh, the specific composition of the controlling entity of the financial controls provided in groups that correspond to levels (from lowest to highest) national public financial control: 1) farm (control and audit, financial departments, the internal audit, and others.); 2) departmental (state programs performers); 3) inter-ministerial (state-coordinators customers, government customers state programs); 4) Government (Cabinet of Ministers of Ukraine); 5) Parliament (Verkhovna Rada of Ukraine, the Accounting Chamber). It was concluded that financial control at the stage of sanctioning of financing of state target programs is complex, systemic financial and legal institution that is potentially suitable for use interested subjects in the distribution of public funds for program objectives and measures to ensure the legality, expediency and rationality effectiveness of such financial distribution activities.